Abundance analysis of barium stars. Issue Volume 9:Issue S298(2013) (6th January 2014) - Yang, Guochao; Liang, Yanchun; Cui, Wenyuan; Zhang, Bo
Abstract: We obtained the chemical abundances of more than 20 Barium (Ba) stars by analysing high resolution echelle spectra. They show obvious overabundances of neutron capture process elements, such as Y, Zr, Ba, La and Eu. Their abundance pattern can be explained by binary accretion through stellar wind, where the Ba stars have accreted the ejecta from the companion stars which were in AGB stages at that time and now evolve as white dwarfs.